Probing the contacts of a low-affinity substrate with a membrane-embedded transport protein using 1H-13C cross-polarisation magic-angle spinning solid-state NMR. (March 2013) - PatchinG, Simon G.; Henderson, Peter J. F.; Sharples, David J.; Middleton, David A.
Abstract Solid-state NMR combined with sample deuteration was used to probe the proximity of the low-affinity substrate D-glucose to its binding site within the Escherichia coli sugar transport protein GalP. Samples of E. coli inner membranes with amplified expression of GalP were incubated in D2O with D-[13C6]glucose and 13C NMR signals from the substrate were assigned in two-dimensional dipolar-assisted rotational resonance (DARR) spectra. The signals were confirmed as representing D-glucose bound to GalP as the peaks were abolished after the substrate was displaced from the specific site with the inhibitor forskolin. The 13C chemical shift values for D-[13C6]glucose in solution revealed some differences compared to those for ligand bound to GalP, the differences being most pronounced for positions C1 and C2, and especially for C1 in the α-anomer. 13C cross-polarization build-up was measured for C1 and C2 of D-[13C6]glucose and D-[2H7, 13C6]glucose in GalP membranes suspended in D2O. The build-up curves for the deuterated substrate reflect intermolecular 1H-13C interactions between the protein and the fully deuterated substrate; the signal build-up suggests that the α-anomer is situated closer to the protein binding site than is the β-anomer, consistent with its relatively high signal intensities and more pronounced chemical shift changes in the 2D-correlation spectra. These results demonstrate the utility of solid-state NMR combined with sample deuteration for mapping the binding interface of low affinity ligands with membrane proteins.